2022
DOI: 10.1093/esr/jcac021
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Employment, Employee Representation, and Employer-Paid Training: A Comparative Analysis

Abstract: This article examines the moderating role of employee representation on the chances of receiving employer-paid training among temporary and permanent workers from a cross-country, comparative perspective. The impact of employee representation is considered at the individual level and at the country level. The statistical analyses are performed using data from the 2015 European Working Conditions Survey and multilevel modelling. Our results suggest that temporary workers receive less employer-paid training than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
0
4
0
5
Order By: Relevance
“…The second is linked to findings demonstrating differing returns to the training and skills between contractual groups, suggesting that even with equal exposure to training and potentially comparable skills, temporary workers tend not to be in a position to take full advantage of their competencies. The third is related to the fact that trade unions seem to have a role in shaping wage returns for permanent and temporary workers differently; that is, even if workforce representation in the workplace promotes learning opportunities regardless of contractual status, trade union coverage at the national level is more beneficial to permanent workers (Adolfsson et al, 2022). More broadly, our analysis points toward the institutional conditionality of the consequences of technological change.…”
Section: Contribution: Ict Skill Usage and Institutional Cleavagesmentioning
confidence: 99%
“…The second is linked to findings demonstrating differing returns to the training and skills between contractual groups, suggesting that even with equal exposure to training and potentially comparable skills, temporary workers tend not to be in a position to take full advantage of their competencies. The third is related to the fact that trade unions seem to have a role in shaping wage returns for permanent and temporary workers differently; that is, even if workforce representation in the workplace promotes learning opportunities regardless of contractual status, trade union coverage at the national level is more beneficial to permanent workers (Adolfsson et al, 2022). More broadly, our analysis points toward the institutional conditionality of the consequences of technological change.…”
Section: Contribution: Ict Skill Usage and Institutional Cleavagesmentioning
confidence: 99%
“…Furthermore, there is evidence that workers prefer to invest in general skills rather than in organization-specific skills (Green 1993;Wang and Barney 2006;Schindler, Weiss and Hubert 2011;Sweeney and Martindale 2012;Kyndt and Baert 2013;Kamphuis and Glebbeek 2020). Research has also found a training gap between workers on temporary contracts and those with open-ended contracts (Adolfsson, Baranowska-Rataj and Lundmark 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It places a strong focus on workers' continuous training and lifelong learning. Even though the principle of a vignette study is to place respondents in a hypothetical situation to reduce the influence of other (real-life) factors, the training preferences of the respondents may be affected by institutional setting, reflecting formal labour market policies, such as the level of employment protection, employee representation and cultural norms related to learning (Benda 2019;Bratti, Conti and Sulis 2021;Adolfsson, Baranowska-Rataj and Lundmark 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certains auteurs ont aussi montré que les travailleurs investissent plus volontiers dans l'acquisition de compétences générales que dans l'acquisition de compétences spécifiques à une organisation (Green, 1993;Wang et Barney, 2006;Schindler, Weiss et Hubert, 2011;Sweeney et Martindale, 2012;Kyndt et Baert, 2013;Kamphuis et Glebbeek, 2020). Enfin, d'autres ont constaté que les travailleurs temporaires avaient moins accès à la formation que leurs collègues titulaires d'un contrat à durée indéterminée (Adolfsson, Baranowska-Rataj et Lundmark, 2022).…”
Section: Introductionunclassified